(untitled) (Research, Society and Development, 2020)
This research aimed to investigate the relationships that exist between human actions and the emergence of new diseases. In addition, discuss what actions, carried out mainly by Environmental Engineers, that can be performed in the face of this problem. For that, it focused on two environmental problems: handling of wild animals and deforestation. The study was of a theoretical character, having as methodology the reading and analysis of published works on the treated themes, in an attempt to articulate with the emergence of Sars-Cov-2. As a result, it was observed that environmental impacts caused by anthropic action are closely related to the emergence and spread of diseases. As an example, Covid-19 stands out, which may have arisen due to non-compliance with biosafety standards in the Wuhan market, in China. It was concluded that if the ways in which we have interacted with nature are not rethought, there is the possibility of new pandemics emerging. In this way, the role of professionals, such as environmental engineers, to mitigate environmental impacts and, consequently, new disease outbreaks, becomes essential.